2020
DOI: 10.1371/journal.pone.0234388
|View full text |Cite
|
Sign up to set email alerts
|

Potential research participants’ use of information during the consent process: A qualitative pilot study of patients enrolled in a clinical trial

Abstract: There is increasing evidence that clinical trial participants are uninformed about the trials in which they participate, raising ethical concerns regarding informed consent. The aim of this pilot study was to explore clinical trial participants' use of consent discussions and information sheets when considering participating in clinical trials research. A qualitative, interview-based pilot study was designed in order to elicit, through dialogue, details of the reasons for participants' use of, and preferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Similarly, our analysis found that brief and timely information about the surveillance protocols and transparent and easy communication with the test teams helps to build trust and to encourage participation and thus were perceived to be important and helpful in implementing the intervention. In a study of participants' use of and preferences on different types of information provision, Jenkins et al found that a high level of trust in medical staff might be a reason for not seeking more information about the study (26). In a casestudy Enria et al showed that an approach to participants that entails active and inclusive dialogue, rather than topdown communications, helped to build up trust in the trial teams and, therefore, engagement and participation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our analysis found that brief and timely information about the surveillance protocols and transparent and easy communication with the test teams helps to build trust and to encourage participation and thus were perceived to be important and helpful in implementing the intervention. In a study of participants' use of and preferences on different types of information provision, Jenkins et al found that a high level of trust in medical staff might be a reason for not seeking more information about the study (26). In a casestudy Enria et al showed that an approach to participants that entails active and inclusive dialogue, rather than topdown communications, helped to build up trust in the trial teams and, therefore, engagement and participation (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, including such information would be at odds with some participants in the qualitative study reporting that the amount of information received prior to recruitment was 'overwhelming', and other research that suggests that participants prefer shorter versions of the PIS and that some participants only minimally use the PIS prior to consent. 100,101 Other studies have also reported that participants overestimate the benefits, and underestimate the risks, of participating in research; 102,103 however, to our knowledge, this is the first time that this has been described in those participating in a fertility trial. In this trial, underestimation of the potential harms may have been exacerbated by the timesensitive nature of fertility treatment; both clinicians and patients have been reported to feel the need to improve the outcomes of treatment immediately following a failed treatment cycle.…”
Section: Evidence In the Context Of Other Similar Studiesmentioning
confidence: 82%
“…Including this information in the PIS is at odds with participants in this study stating that the information provided to them was 'overwhelming', and other research that suggests that participants prefer shorter information sheets 101 and that participants only minimally use the PIS. 100 However, future research should seek trial participants' views on how evidence regarding the potential harms of a procedure, or at least the unknowns, should be imparted, including the medium (i.e. PIS or face to face) and how the information should be structured in order to not unnecessarily perturb potential participants about participating in research.…”
Section: Implications For Future Research Needsmentioning
confidence: 99%
“…29 Consequently, crucial information may be difficult to find, and the form is seldom read anyway. 30…”
Section: Discussionmentioning
confidence: 99%
“…29 Consequently, crucial information may be difficult to find, and the form is seldom read anyway. 30 Although there appears to be agreement on the essential elements of informed consent, the degree of information that an ICF should offer is controversial. [31][32][33] Some critiques express concerns regarding excessive details on certain elements, many of which go beyond what is important to decision-making and may distract potential research participants from more crucial information.…”
Section: Discussionmentioning
confidence: 99%